Parents’ opinion about the use of music in the neonatal environment (Research, Society and Development, 2022)
Objective: Reveal the opinion of parents in relation to the use of music in the neonatal environment. Method: This is all descriptive, cross-sectional with a qualitative approach, carried out with parents of newborns hospitalized in the Neonatal unit of a teaching hospital, located in the Northern Region of the State of Paraná. Data were collected in June and July 2019 and analyzed through Thematic Content Analysis.  Results: Participated in the study eight parents. After analysis and interpretation of the collected data, two thematic units emerged: Experiencing music in the neonatal environment, which results in or in the following categories; First contact with music; Benefits and harms of music, The Second thematic unit: Absence of music in the neonatal environment that resulted in the category: Stress and anxiety in the face of the neonatal environment without music. Final considerations: Music helps reduce anxiety, stress and relaxation, and provides a more pleasant environment.